2021
DOI: 10.1101/2021.11.04.467261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid ecological and evolutionary divergence during a poleward range expansion

Abstract: Anthropogenic climate change is rapidly altering ecosystems, driving range shifts, range contractions, dwindling population sizes and local extinctions in many species. Some species, however, are expanding their ranges and seem to benefit from warming temperatures. This is the case for the wasp spider, Argiope bruennichi, which has undergone a range expansion from its historic range in the Mediterranean (“core”), now reaching as far as the Baltic states and Scandinavia (“edge”). The rate of this range expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 134 publications
0
4
0
Order By: Relevance
“…Nevertheless, sub‐lethal injuries from prolonged cold exposure may accumulate and affect winter survival (Marshall & Sinclair, 2012), although studies on such effects in seemingly freeze‐avoidant animals are rare. Existing studies have shown lack of accumulated effects in two nymphalid butterflies (Pullin & Bale, 1989) but also substantial mortality in temperatures well above supercooling points in the spider Argiope bruennichi (Sheffer et al, 2021, preprint) and the spruce budworm Choristoneura fumiferana (Marshall & Sinclair, 2015; but see Delisle et al, 2022). Marshall and Sinclair (2015) also demonstrated strong effects of repeated cold exposure, which may have operated in our experiment too, given our fluctuating temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, sub‐lethal injuries from prolonged cold exposure may accumulate and affect winter survival (Marshall & Sinclair, 2012), although studies on such effects in seemingly freeze‐avoidant animals are rare. Existing studies have shown lack of accumulated effects in two nymphalid butterflies (Pullin & Bale, 1989) but also substantial mortality in temperatures well above supercooling points in the spider Argiope bruennichi (Sheffer et al, 2021, preprint) and the spruce budworm Choristoneura fumiferana (Marshall & Sinclair, 2015; but see Delisle et al, 2022). Marshall and Sinclair (2015) also demonstrated strong effects of repeated cold exposure, which may have operated in our experiment too, given our fluctuating temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Programmed environmental chambers provide the additional benefit of being able to test realistic thermal regimes from any geographic position or point in time independent of physical location. While some laboratory studies have simulated detailed and realistic thermal regimes (Bradshaw et al, 2004 ; Maguire et al, 2015 ; Sheffer et al, 2021 ; Williams et al, 2015 ), we are unaware of other studies using growth chambers to simulate different, realistic, climate change scenarios for multiple locations. This is likely in part because its feasibility depends on modern environmental chamber control software and a study system with some a priori knowledge of phenology, but we encourage this design as a means of increasing the realism of climate change ecophysiology studies in controlled experimental settings.…”
Section: Discussionmentioning
confidence: 99%
“…While other environmental factors that potentially contribute to changes in development and fitness (e.g., light, nutrient resources, water availability, air flow) are controlled in this type of growth chamber simulation, this allows for the effect of future temperature regimes on development and fitness to be evaluated independently. Despite its potential, however, the use of realistic temperature regimes in growth chamber has been underutilized (but see Bradshaw et al, 2004 ; Maguire et al, 2015 ; Sheffer et al, 2021 ; Williams et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A comparison with A. bruennichi populations in southern Europe might be revealing here. Argiope bruennichi has undergone a massive range expansion during the last decades and only recently colonized northern Europe, including northern Germany, probably due to adaptive introgression, and facilitated by global warming (Kumschick et al 2011; Sheffer et al 2021). The mating season at the northern range of the species' distribution is very short with a peak mating period of about two weeks (Zimmer et al 2012).…”
mentioning
confidence: 99%